Isolation,Characterization And Preliminary Pharmacological Evaluation Of Constituents Of Garcinia Cowa Roxb - Sri Wahyuni, Fatma (2009)

(untitled)
Preliminary screening for in vitro cytotoxic and inhibition nitric oxide (NO) production acivities were carried out on fourteen extracts of different parts of eight Garcinia species. These extracts were evaluated for cytotoxic activity using microculture tetrazolium, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay by measuring the reduction of viability of cell cultures in the presence and absence of the extracts. Four type of cancer cell lines, HL-60 (leukemia), MCF-7 (breast), DU-145 (prostate) and NCI-H460 (non-small cell lung) were used for a preliminary picture of extracts selectivity profile. NO inhibition (in lipopolysaccharide (LPS)-activated macrophages) activity was evaluated using Griess assay. Extract of the stem bark from G. cowa Roxb showed selective cytotoxicity towards NCI- H460 (IC50 = 11 μg/mL). The extract also exhibited inhibition of NO production (IC50= 25 μg/mL) without being cytotoxic to RAW 264.7 cells. Based on these promising selective cytotoxicity towards NCI-H460 and NO inhibitory activities, G. cowa was selected for further studies on the isolation and identification its active components.